Isolation of Arcanobacterium (Actinomyces) pyogenes from abscessed cattle kidney and identification by PCR - Ertas, HB; Kiliç, A; Özbey, G; Muz, A (Tubitak Scientific & Technological Research Council Turkey, 2005)
In this study, the presence of Arcanobacterium spp., which causes a variety of purulent infections involving the skin. joints and visceral organs, was investigated in abscessed kidney samples of cattle. A total of 500 cattle were examined at postmortem and 100 samples with abscess were collected. Arcanobacterium pyogenes was isolated in 40 (40%) of the samples examined. DNA extracted from the isolates were amplified by Polymerase Chain Reaction (PCR) using specific primers derived from plo gene of A. pyogenes and all the isolates were determined to be positive by PCR. It was concluded that PCR employed in this study may be applied for identification of A. pyogenes.
Keywords: Arcanobacterium pyogenes; PCR; cattle; kidney